Built with Alectryon, running Coq+SerAPI v8.10.0+0.7.0. Coq sources are in this panel; goals and messages will appear in the other. Bubbles () indicate interactive fragments: hover for details, tap to reveal contents. Use Ctrl+↑ Ctrl+↓ to navigate, Ctrl+🖱️ to focus.
Before getting started, we need to import all of our
definitions from the previous chapter:
From LF Require Export Basics.
For the Require Export to work, Coq needs to be able to
find a compiled version of Basics.v, called Basics.vo, in a directory
associated with the prefix LF. This file is analogous to the .class
files compiled from .java source files and the .o files compiled from
.c files.
First create a file named _CoqProject containing the following line
(if you obtained the whole volume "Logical Foundations" as a single
archive, a _CoqProject should already exist and you can skip this step):
-Q . LF
This maps the current directory (".", which contains Basics.v,
Induction.v, etc.) to the prefix (or "logical directory") "LF".
PG and CoqIDE read _CoqProject automatically, so they know to where to
look for the file Basics.vo corresponding to the library LF.Basics.
Once _CoqProject is thus created, there are various ways to build
Basics.vo:
If you have trouble (e.g., if you get complaints about missing
identifiers later in the file), it may be because the "load path"
for Coq is not set up correctly. The Print LoadPath. command
may be helpful in sorting out such issues.
In particular, if you see a message like
Compiled library Foo makes inconsistent assumptions over
library Bar
check whether you have multiple installations of Coq on your machine.
It may be that commands (like coqc) that you execute in a terminal
window are getting a different version of Coq than commands executed by
Proof General or CoqIDE.
One more tip for CoqIDE users: If you see messages like Error:
Unable to locate library Basics, a likely reason is
inconsistencies between compiling things within CoqIDE vs using
coqc from the command line. This typically happens when there
are two incompatible versions of coqc installed on your
system (one associated with CoqIDE, and one associated with coqc
from the terminal). The workaround for this situation is
compiling using CoqIDE only (i.e. choosing "make" from the menu),
and avoiding using coqc directly at all.
- In Proof General: The compilation can be made to happen automatically
when you submit the Require line above to PG, by setting the emacs
variable coq-compile-before-require to t.
- In CoqIDE: Open Basics.v; then, in the "Compile" menu, click
on "Compile Buffer".
- From the command line: Generate a Makefile using the coq_makefile
utility, that comes installed with Coq (if you obtained the whole
volume as a single archive, a Makefile should already exist
and you can skip this step):
- Another common reason is that the library Bar was modified and recompiled without also recompiling Foo which depends on it. Recompile Foo, or everything if too many files are affected. (Using the third solution above: make clean; make.)
(* ################################################################# *)
We proved in the last chapter that 0 is a neutral element
for + on the left, using an easy argument based on
simplification. We also observed that proving the fact that it is
also a neutral element on the right...
forall n : nat, n = n + 0
... can't be done in the same simple way. Just applying
reflexivity doesn't work, since the n in n + 0 is an arbitrary
unknown number, so the match in the definition of + can't be
simplified.
forall n : nat, n = n + 0n:natn = n + 0Abort.n:natn = n + 0
And reasoning by cases using destruct n doesn't get us much
further: the branch of the case analysis where we assume n = 0
goes through fine, but in the branch where n = S n' for some n' we
get stuck in exactly the same way.
forall n : nat, n = n + 0forall n : nat, n = n + 0n:natn = n + 0n:natE:n = 00 = 0 + 0n, n':natE:n = S n'S n' = S n' + 0reflexivity. (* so far so good... *)n:natE:n = 00 = 0 + 0n, n':natE:n = S n'S n' = S n' + 0Abort.n, n':natE:n = S n'S n' = S (n' + 0)
We could use destruct n' to get one step further, but,
since n can be arbitrarily large, if we just go on like this
we'll never finish.
To prove interesting facts about numbers, lists, and other
inductively defined sets, we usually need a more powerful
reasoning principle: induction.
Recall (from high school, a discrete math course, etc.) the
principle of induction over natural numbers: If P(n) is some
proposition involving a natural number n and we want to show
that P holds for all numbers n, we can reason like this:
In Coq, the steps are the same: we begin with the goal of proving
P(n) for all n and break it down (by applying the induction
tactic) into two separate subgoals: one where we must show P(O)
and another where we must show P(n') → P(S n'). Here's how
this works for the theorem at hand:
- show that P(O) holds;
- show that, for any n', if P(n') holds, then so does P(S n');
- conclude that P(n) holds for all n.
forall n : nat, n = n + 0forall n : nat, n = n + 0n:natn = n + 00 = 0 + 0n':natIHn':n' = n' + 0S n' = S n' + 0reflexivity.0 = 0 + 0n':natIHn':n' = n' + 0S n' = S n' + 0n':natIHn':n' = n' + 0S n' = S (n' + 0)reflexivity. Qed.n':natIHn':n' = n' + 0S n' = S n'
Like destruct, the induction tactic takes an as...
clause that specifies the names of the variables to be introduced
in the subgoals. Since there are two subgoals, the as... clause
has two parts, separated by |. (Strictly speaking, we can omit
the as... clause and Coq will choose names for us. In practice,
this is a bad idea, as Coq's automatic choices tend to be
confusing.)
In the first subgoal, n is replaced by 0. No new variables
are introduced (so the first part of the as... is empty), and
the goal becomes 0 = 0 + 0, which follows by simplification.
In the second subgoal, n is replaced by S n', and the
assumption n' + 0 = n' is added to the context with the name
IHn' (i.e., the Induction Hypothesis for n'). These two names
are specified in the second part of the as... clause. The goal
in this case becomes S n' = (S n') + 0, which simplifies to
S n' = S (n' + 0), which in turn follows from IHn'.
forall n : nat, n - n = 0(* WORKED IN CLASS *)forall n : nat, n - n = 0n:natn - n = 00 - 0 = 0n':natIHn':n' - n' = 0S n' - S n' = 00 - 0 = 0reflexivity.0 = 0n':natIHn':n' - n' = 0S n' - S n' = 0n':natIHn':n' - n' = 0n' - n' = 0reflexivity. Qed.n':natIHn':n' - n' = 00 = 0
(The use of the intros tactic in these proofs is actually
redundant. When applied to a goal that contains quantified
variables, the induction tactic will automatically move them
into the context as needed.)
Exercise: 2 stars, standard, recommended (basic_induction)
forall n : nat, n * 0 = 0(* FILL IN HERE *) Admitted.forall n : nat, n * 0 = 0forall n m : nat, S (n + m) = n + S m(* FILL IN HERE *) Admitted.forall n m : nat, S (n + m) = n + S mforall n m : nat, n + m = m + n(* FILL IN HERE *) Admitted.forall n m : nat, n + m = m + nforall n m p : nat, n + (m + p) = n + m + p(* FILL IN HERE *) Admitted.forall n m p : nat, n + (m + p) = n + m + p
☐
Exercise: 2 stars, standard (double_plus)
Fixpoint double (n:nat) :=
match n with
| O => O
| S n' => S (S (double n'))
end.
Use induction to prove this simple fact about double:
forall n : nat, double n = n + n(* FILL IN HERE *) Admitted.forall n : nat, double n = n + n
☐
Exercise: 2 stars, standard, optional (evenb_S)
forall n : nat, evenb (S n) = negb (evenb n)(* FILL IN HERE *) Admitted.forall n : nat, evenb (S n) = negb (evenb n)
☐
Exercise: 1 star, standard (destruct_induction)
(* Do not modify the following line: *) Definition manual_grade_for_destruct_induction : option (nat*string) := None.
☐
(* ################################################################# *)
In Coq, as in informal mathematics, large proofs are often
broken into a sequence of theorems, with later proofs referring to
earlier theorems. But sometimes a proof will require some
miscellaneous fact that is too trivial and of too little general
interest to bother giving it its own top-level name. In such
cases, it is convenient to be able to simply state and prove the
needed "sub-theorem" right at the point where it is used. The
assert tactic allows us to do this. For example, our earlier
proof of the mult_0_plus theorem referred to a previous theorem
named plus_O_n. We could instead use assert to state and
prove plus_O_n in-line:
forall n m : nat, (0 + n) * m = n * mforall n m : nat, (0 + n) * m = n * mn, m:nat(0 + n) * m = n * mn, m:nat0 + n = nn, m:natH:0 + n = n(0 + n) * m = n * mreflexivity.n, m:nat0 + n = nn, m:natH:0 + n = n(0 + n) * m = n * mreflexivity. Qed.n, m:natH:0 + n = nn * m = n * m
The assert tactic introduces two sub-goals. The first is
the assertion itself; by prefixing it with H: we name the
assertion H. (We can also name the assertion with as just as
we did above with destruct and induction, i.e., assert (0 + n
= n) as H.) Note that we surround the proof of this assertion
with curly braces { ... }, both for readability and so that,
when using Coq interactively, we can see more easily when we have
finished this sub-proof. The second goal is the same as the one
at the point where we invoke assert except that, in the context,
we now have the assumption H that 0 + n = n. That is,
assert generates one subgoal where we must prove the asserted
fact and a second subgoal where we can use the asserted fact to
make progress on whatever we were trying to prove in the first
place.
Another example of assert...
For example, suppose we want to prove that (n + m) + (p + q)
= (m + n) + (p + q). The only difference between the two sides of
the = is that the arguments m and n to the first inner +
are swapped, so it seems we should be able to use the
commutativity of addition (plus_comm) to rewrite one into the
other. However, the rewrite tactic is not very smart about
where it applies the rewrite. There are three uses of + here,
and it turns out that doing rewrite → plus_comm will affect
only the outer one...
forall n m p q : nat, n + m + (p + q) = m + n + (p + q)forall n m p q : nat, n + m + (p + q) = m + n + (p + q)(* We just need to swap (n + m) for (m + n)... seems like plus_comm should do the trick! *)n, m, p, q:natn + m + (p + q) = m + n + (p + q)(* Doesn't work...Coq rewrites the wrong plus! *) Abort.n, m, p, q:natp + q + (n + m) = m + n + (p + q)
To use plus_comm at the point where we need it, we can introduce
a local lemma stating that n + m = m + n (for the particular m
and n that we are talking about here), prove this lemma using
plus_comm, and then use it to do the desired rewrite.
forall n m p q : nat, n + m + (p + q) = m + n + (p + q)forall n m p q : nat, n + m + (p + q) = m + n + (p + q)n, m, p, q:natn + m + (p + q) = m + n + (p + q)n, m, p, q:natn + m = m + nn, m, p, q:natH:n + m = m + nn + m + (p + q) = m + n + (p + q)n, m, p, q:natn + m = m + nreflexivity.n, m, p, q:natm + n = m + nn, m, p, q:natH:n + m = m + nn + m + (p + q) = m + n + (p + q)reflexivity. Qed. (* ################################################################# *)n, m, p, q:natH:n + m = m + nm + n + (p + q) = m + n + (p + q)
"Informal proofs are algorithms; formal proofs are code."
What constitutes a successful proof of a mathematical claim?
The question has challenged philosophers for millennia, but a
rough and ready definition could be this: A proof of a
mathematical proposition P is a written (or spoken) text that
instills in the reader or hearer the certainty that P is true --
an unassailable argument for the truth of P. That is, a proof
is an act of communication.
Acts of communication may involve different sorts of readers. On
one hand, the "reader" can be a program like Coq, in which case
the "belief" that is instilled is that P can be mechanically
derived from a certain set of formal logical rules, and the proof
is a recipe that guides the program in checking this fact. Such
recipes are formal proofs.
Alternatively, the reader can be a human being, in which case the
proof will be written in English or some other natural language,
and will thus necessarily be informal. Here, the criteria for
success are less clearly specified. A "valid" proof is one that
makes the reader believe P. But the same proof may be read by
many different readers, some of whom may be convinced by a
particular way of phrasing the argument, while others may not be.
Some readers may be particularly pedantic, inexperienced, or just
plain thick-headed; the only way to convince them will be to make
the argument in painstaking detail. But other readers, more
familiar in the area, may find all this detail so overwhelming
that they lose the overall thread; all they want is to be told the
main ideas, since it is easier for them to fill in the details for
themselves than to wade through a written presentation of them.
Ultimately, there is no universal standard, because there is no
single way of writing an informal proof that is guaranteed to
convince every conceivable reader.
In practice, however, mathematicians have developed a rich set of
conventions and idioms for writing about complex mathematical
objects that -- at least within a certain community -- make
communication fairly reliable. The conventions of this stylized
form of communication give a fairly clear standard for judging
proofs good or bad.
Because we are using Coq in this course, we will be working
heavily with formal proofs. But this doesn't mean we can
completely forget about informal ones! Formal proofs are useful
in many ways, but they are not very efficient ways of
communicating ideas between human beings.
For example, here is a proof that addition is associative:
forall n m p : nat, n + (m + p) = n + m + pforall n m p : nat, n + (m + p) = n + m + pn, m, p:natn + (m + p) = n + m + pm, p:nat0 + (m + p) = 0 + m + pn', m, p:natIHn':n' + (m + p) = n' + m + pS n' + (m + p) = S n' + m + pn', m, p:natIHn':n' + (m + p) = n' + m + pS n' + (m + p) = S n' + m + pn', m, p:natIHn':n' + (m + p) = n' + m + pS (n' + (m + p)) = S (n' + m + p)reflexivity. Qed.n', m, p:natIHn':n' + (m + p) = n' + m + pS (n' + m + p) = S (n' + m + p)
Coq is perfectly happy with this. For a human, however, it
is difficult to make much sense of it. We can use comments and
bullets to show the structure a little more clearly...
forall n m p : nat, n + (m + p) = n + m + pforall n m p : nat, n + (m + p) = n + m + pn, m, p:natn + (m + p) = n + m + pm, p:nat0 + (m + p) = 0 + m + pn', m, p:natIHn':n' + (m + p) = n' + m + pS n' + (m + p) = S n' + m + preflexivity.m, p:nat0 + (m + p) = 0 + m + pn', m, p:natIHn':n' + (m + p) = n' + m + pS n' + (m + p) = S n' + m + pn', m, p:natIHn':n' + (m + p) = n' + m + pS (n' + (m + p)) = S (n' + m + p)reflexivity. Qed.n', m, p:natIHn':n' + (m + p) = n' + m + pS (n' + m + p) = S (n' + m + p)
... and if you're used to Coq you may be able to step
through the tactics one after the other in your mind and imagine
the state of the context and goal stack at each point, but if the
proof were even a little bit more complicated this would be next
to impossible.
A (pedantic) mathematician might write the proof something like
this:
- Theorem: For any n, m and p,
- First, suppose n = 0. We must show
- Next, suppose n = S n', where
- First, suppose n = 0. We must show
The overall form of the proof is basically similar, and of
course this is no accident: Coq has been designed so that its
induction tactic generates the same sub-goals, in the same
order, as the bullet points that a mathematician would write. But
there are significant differences of detail: the formal proof is
much more explicit in some ways (e.g., the use of reflexivity)
but much less explicit in others (in particular, the "proof state"
at any given point in the Coq proof is completely implicit,
whereas the informal proof reminds the reader several times where
things stand).
Exercise: 2 stars, advanced, recommended (plus_comm_informal)
(* Do not modify the following line: *) Definition manual_grade_for_plus_comm_informal : option (nat*string) := None.
☐
Exercise: 2 stars, standard, optional (eqb_refl_informal)
(* ################################################################# *)
Exercise: 3 stars, standard, recommended (mult_comm)
forall n m p : nat, n + (m + p) = m + (n + p)(* FILL IN HERE *) Admitted.forall n m p : nat, n + (m + p) = m + (n + p)
Now prove commutativity of multiplication. (You will probably
need to define and prove a separate subsidiary theorem to be used
in the proof of this one. You may find that plus_swap comes in
handy.)
forall m n : nat, m * n = n * m(* FILL IN HERE *) Admitted.forall m n : nat, m * n = n * m
☐
Exercise: 3 stars, standard, optional (more_exercises)
forall n : nat, true = (n <=? n)(* FILL IN HERE *) Admitted.forall n : nat, true = (n <=? n)forall n : nat, (0 =? S n) = false(* FILL IN HERE *) Admitted.forall n : nat, (0 =? S n) = falseforall b : bool, b && false = false(* FILL IN HERE *) Admitted.forall b : bool, b && false = falseforall n m p : nat, (n <=? m) = true -> (p + n <=? p + m) = true(* FILL IN HERE *) Admitted.forall n m p : nat, (n <=? m) = true -> (p + n <=? p + m) = trueforall n : nat, (S n =? 0) = false(* FILL IN HERE *) Admitted.forall n : nat, (S n =? 0) = falseforall n : nat, 1 * n = n(* FILL IN HERE *) Admitted.forall n : nat, 1 * n = nforall b c : bool, b && c || (negb b || negb c) = true(* FILL IN HERE *) Admitted.forall b c : bool, b && c || (negb b || negb c) = trueforall n m p : nat, (n + m) * p = n * p + m * p(* FILL IN HERE *) Admitted.forall n m p : nat, (n + m) * p = n * p + m * pforall n m p : nat, n * (m * p) = n * m * p(* FILL IN HERE *) Admitted.forall n m p : nat, n * (m * p) = n * m * p
☐
Exercise: 2 stars, standard, optional (eqb_refl)
forall n : nat, true = (n =? n)(* FILL IN HERE *) Admitted.forall n : nat, true = (n =? n)
☐
Exercise: 2 stars, standard, optional (plus_swap')
forall n m p : nat, n + (m + p) = m + (n + p)(* FILL IN HERE *) Admitted.forall n m p : nat, n + (m + p) = m + (n + p)
☐
Exercise: 3 stars, standard, recommended (binary_commute)
(* FILL IN HERE *) (* Do not modify the following line: *) Definition manual_grade_for_binary_commute : option (nat*string) := None.
☐
Exercise: 5 stars, advanced (binary_inverse)
Admitted.nat_to_bin:nat -> binn:natbin
Prove that, if we start with any nat, convert it to binary, and
convert it back, we get the same nat we started with. (Hint: If
your definition of nat_to_bin involved any extra functions, you
may need to prove a subsidiary lemma showing how such functions
relate to nat_to_bin.)
forall n : nat, bin_to_nat (nat_to_bin n) = n(* FILL IN HERE *) Admitted. (* Do not modify the following line: *) Definition manual_grade_for_binary_inverse_a : option (nat*string) := None.forall n : nat, bin_to_nat (nat_to_bin n) = n
(b) One might naturally expect that we should also prove the
opposite direction -- that starting with a binary number,
converting to a natural, and then back to binary should yield
the same number we started with. However, this is not the
case! Explain (in a comment) what the problem is.
(* FILL IN HERE *) (* Do not modify the following line: *) Definition manual_grade_for_binary_inverse_b : option (nat*string) := None.
(c) Define a normalization function -- i.e., a function
normalize going directly from bin to bin (i.e., not by
converting to nat and back) such that, for any binary number
b, converting b to a natural and then back to binary yields
(normalize b). Prove it. (Warning: This part is a bit
tricky -- you may end up defining several auxiliary lemmas.
One good way to find out what you need is to start by trying
to prove the main statement, see where you get stuck, and see
if you can find a lemma -- perhaps requiring its own inductive
proof -- that will allow the main proof to make progress.) Don't
define thi using nat_to_bin and bin_to_nat!
(* FILL IN HERE *) (* Do not modify the following line: *) Definition manual_grade_for_binary_inverse_c : option (nat*string) := None.
☐
(* Wed Jan 9 12:02:44 EST 2019 *)